Asymmetric information in the hong kong forward property market - Leung, Barbara Y. P.; Hui, Eddie C. M.; Seabrooke, Bill (International Journal of Strategic Property Management, 2010)
Use of forward contracts for pre‐selling uncompleted properties is becoming popular in many countries. However, there have been limited researches investigating the risks arising from asymmetric information specific to buying a presale property and the critical factors required for the development of an effective forward property market. Hong Kong is one of the largest forward property markets in the world and it has been getting mature after half‐a‐century long development. This paper therefore aims to study the asymmetric information problem found in the forward property markets in different areas and explores the set of factors that are critical to the development of a forward property market by referencing the development of the Hong Kong forward property market. First published online: 18 Oct 2010